Benchmarking modelling in the context of banking sector deepening and long-term economic growth - Al-Moulani, Ali; Alexiou, Constantinos (Center for Promoting Ideas (CPI), 2021)
This paper identifies a host of key factors that influence the development of the banking sector as well as enhances our understanding of benchmarking modelling as a means of stimulating economic growth. A novel benchmarking method is utilized that assesses the level of banking sector depth in a country against its counterparts in the top quartile countries using mixed effects and system GMM for dynamic panel data models. The results suggest that the development of the banking sector is contingent upon factors that can be traced within the structure of the sector, the macroeconomic environment as well as the governing, institutional, and legal frameworks. The paper presents four benchmarking models that potentially provide policymakers with tools to benchmark the levels of banking sector development against their peers in countries in which the particular sector contributes significantly to economic growth.
Keywords: Banking sector depth; Benchmarking; Economic Growth